2021
DOI: 10.1093/ageing/afab224
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vaccination on the spread of SARS-CoV-2 infection in north-east Italy nursing homes. A propensity score and risk analysis

Abstract: Background In the Veneto Region, 421,000 coronavirus 2019 disease (COVID-19) cases and 11,000 deaths have been reported since 21 February 2020. The pandemic spread particularly in nursing homes (NH). Objective This study estimated the impact of SARS-CoV-2 infection among NH residents, focusing on the risk of hospitalisation and death due to COVID-19 compared with the general older population. It also provided evidence of risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…22 A previous study on the risk of infection, hospitalization and mortality due to COVID-19 in nursing home residents, compared to matched non-nursing home counterparts has shown how people in this setting were at a significantly increased risk of any of the three outcomes, especially in the first and second pandemic waves. 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A previous study on the risk of infection, hospitalization and mortality due to COVID-19 in nursing home residents, compared to matched non-nursing home counterparts has shown how people in this setting were at a significantly increased risk of any of the three outcomes, especially in the first and second pandemic waves. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Only after the implementation of the vaccination campaign, starting from nursing home residents and personnel, the impact of subsequent pandemic waves was reduced, at least in terms of mortality. 23 …”
Section: Discussionmentioning
confidence: 99%
“…7,8 To date, most studies on vaccine efficacy in NHs were performed prior to the emergence of the BA.2 variant of SARS-CoV-2 (Omicron) as the dominant strain, and before a third vaccine dose was recommended. [2][3][4][5]9 Moreover, many of these nursing home studies looked at primarily urban as opposed to rural NH populations. 10,11 This report analyzes the effect of prior vaccination of NH residents during recent outbreaks of SARS-CoV-2 in NHs in rural Manitoba, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies on vaccine efficacy in NHs were performed prior to the emergence of the BA.2 variant of SARS‐CoV‐2 (Omicron) as the dominant strain, and before a third vaccine dose was recommended 2–5,9 . Moreover, many of these nursing home studies looked at primarily urban as opposed to rural NH populations 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a 2021 study estimated that in Apulia, an Italian Region with 4 million inhabitants, a proportion of citizens with at least one underling condition to be around 65%; this proportion increases with increasing age [ 23 ]. A 2022 Italian study [ 24 ] reported that, among 852,211 living subjects residing in Veneto Region and aged between 70 and 100 years, the prevalence of subjects with at least one chronic disease ranged from 69% to 74%. Of course, additional studies are needed to estimate these data on whole the Italian population aged 65+ years.…”
mentioning
confidence: 99%